ANALISIS PENGARUH PENDAPATAN DAN KONSUMSI RUMAH TANGGA TERHADAP KESEJAHTERAAN KELUARGA BURUH TANI DI KECAMATAN PAYUNG, BANGKA SELATAN - Sutriyani; Medinal; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2019)
The purpose of this thesis is to determine the impact of Income and household consumption towardsfarmer’s family prosperity, simultanly and partialy. This thesis was conducted by period of March 2019 until June 2019. The method that was used in this thesis is descriptive with quantitative approach with intention to determine the connection between independent variables dan dependent variable using statistics formulation to determine the connection of income and household consumption impact towards farmer’s family prosperity in Payung, South Bangka. While statistics formula that is used to test the hypothesis is multiple linear regression analysis. The number of samples in this thesis is 100 people form 438 people in population. Results of this research proves that: (1) This researchshows significant impact of income variable towards farmer’s family prosperity in Payung, South Bangka. That is proved with thitung>ttabel(8.061>1,98447). (2) This research also shows significant impact between household consumption variable towards farmer’s family prosperityin Payung, South Bangka. That is proved with thitung>ttabel(4.283>1,98447). And (3) there is significant impact ofincome and household consumption variable towards farmer’s family prosperity in Payung, South Bangka. Thas is Proved with Fhitung>Ftabel(245.7>2,11).